Effective E-Da’wah Strategies for Navigating Religious Moderation Campaign in the Era of Digital Disruption - Robeet, Robeet Thadi; Andang Sunarto (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2023)
This article aims to describe the role of e-da'wah in religious moderation campaigns in the era of digital disruption. This study uses a qualitative method with the library research approach. The findings have revealed that, conceptually, religious moderation is a middle attitude, neither secular nor religious. The campaign strategy for religious moderation is to present Islam as a humanist religion, changing the paradigm from qabilah to ummah, and revitalizing Islamic kaffah. Additionally, to gain effective e-da'wah strategies of religious moderation campaigns, da'wah activists should understand the target audience, be able to create interesting content, collaborate with influencers, utilize the latest technology, and build online communities. In short, it is important to continue to adapt to technological developments and look for new ways to convey relevant and useful da'wah messages in this digital era.